2013
DOI: 10.1080/02699931.2013.787972
|View full text |Cite
|
Sign up to set email alerts
|

The indirect effect of attention bias on memory via interpretation bias: Evidence for the combined cognitive bias hypothesis in subclinical depression

Abstract: Little research has investigated functional relations among attention, interpretation, and memory biases in depressed samples. The present study tested the indirect effect of attention bias on memory through interpretation bias as an intervening variable in a mixed sample of non-depressed and subclinically depressed individuals. Subclinically depressed and nondepressed individuals completed a spatial cueing task (to measure attention bias), followed by a scrambled sentences test (to measure interpretation bias… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
70
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 23 publications
2
70
1
1
Order By: Relevance
“…Individual bias acquisition scores were not related to performance on an interpretation test presenting trained (experiment 2a) or non-trained (experiment 2b) stimuli. This is surprising in light of prior research showing that interpretation mediates the relation between attention and memory bias (Everaert et al, 2014;Everaert et al, 2013). Moreover, the pre-training attention bias scores did not predict affective task-switching costs nor the change in interpretation bias.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Individual bias acquisition scores were not related to performance on an interpretation test presenting trained (experiment 2a) or non-trained (experiment 2b) stimuli. This is surprising in light of prior research showing that interpretation mediates the relation between attention and memory bias (Everaert et al, 2014;Everaert et al, 2013). Moreover, the pre-training attention bias scores did not predict affective task-switching costs nor the change in interpretation bias.…”
Section: Discussioncontrasting
confidence: 49%
“…In experiment 2a and 2b, we examined transfer of training toward positive and negative material to trained and non-trained stimuli in an interpretation task requiring individuals to evaluate positive and negative selfrelevant meanings. Interpretation bias, a risk factor to various emotional disorders (Mathews & MacLeod, 2005), depends on emotional biases in attention and regulates emotional memory (Everaert, Duyck, & Koster, 2014;Everaert, Tierens, Uzieblo, & Koster, 2013). In keeping with recent ABM research, we investigated effects of training on attention bias and transfer tasks at the condition as well as at the individual differences level.…”
Section: Transfer Of Single-session Abmmentioning
confidence: 99%
See 1 more Smart Citation
“…To follow up on the findings reported in this article, we recently conducted a study to provide further empirical support for the indirect effect of attention on memory bias via interpretation processes (Everaert, Tierens, Uzieblo, & Koster, 2013). …”
Section: Attention Interpretation and Memory Biases 18mentioning
confidence: 85%
“…In examining the opposite causal direction, White, Suway, Bar-Haim, and Fox (2011) ACCEPTED MANUSCRIPT Running Head: TRAINING INHIBITION OF NEGATIVE INFORMATION 6 showed that participants who were trained to attend to threat displayed an increase in anxiety-related negative interpretations of ambiguous events. Everaert, Tierens, Uzieblo, and Koster, (2013) have found, using a non-depressed and sub-clinically depressed sample, that a negative bias in attention indirectly affects memory via its effect on negative interpretation bias. To the best of our knowledge, the transfer of rumination-related training effects from one bias to another has not been examined.…”
Section: Accepted Manuscriptmentioning
confidence: 99%